If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x-2(-4x+1)=-2
We simplify the equation to the form, which is simple to understand
-8x-2(-4x+1)=-2
Reorder the terms in parentheses
-8x+(+8x-2)=-2
Remove unnecessary parentheses
-8x+8x-2=-2
We move all terms containing x to the left and all other terms to the right.
-8x+8x=-2+2
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| -4x-7(6x+4)=18 | | -4x-(-4x+8)=-3 | | 7(t-3)=2(t-9)+2r | | 6a-11a=7 | | -2x+4(3x)=-10 | | 2x+4+5x+10+3x=84 | | 121x^2+169=0 | | -5x-4(2x+4)=23 | | 4x+2(2x-18)=20 | | -4x-(-4x-12)=12 | | 7x+6(-6x+3)=-11 | | -2x-(-3x-13)=11 | | 15-(3x+8)= | | 12x-2(6x+7)=-14 | | (x+4)(x-3)=5x | | -24x-3(-8x+2)=1 | | -x-4(2)=-5 | | 8(2x-1)-5(2x+3)=-5 | | -8-28=13-9x | | -2x+2(-3x-13)=10 | | (2x-5)2=121 | | 2x+9y=10 | | 8x+32=3x+3 | | 7(1-x)-6(2-x)=8 | | x^3-14x^2+39x+54=0 | | 3a-12a-15=0 | | 5(x+1)+5(x-1)=30 | | x+0.10x+0.05x=40 | | 10m+32m=-5 | | m-3m=-10 | | 3(x-11)(x+10)=0 | | 7(x+10)-3=73 |